Creutzfeldt-Jakob Disease - A Case Report From Jharkhand - Sinha K K; Jha D K (Annals of Indian Academy of Neurology, 2003)
Creutzfeldt-Jakob disease is a neuro-degenerative disorder of central nervous system caused by infectious proteins called ′prions′ and typically presents with progressive dementia and myoclonus. Here, we report a second ′ probable′ case from mid-Eastern region of India.